Design of Web-Based Project Management System with Multi-Level Role-Based Access Control - Zikra, Andi Anzanul; Darnilasari, Aulia; Yanuary, Rahmat; Sari, Komala (Ali Institute of Research and Publication, 2025)
Conventional project management using WhatsApp and email creates problems in progress tracking and inefficient team coordination. Research shows 70% of projects fail to deliver what was promised to customers. This research aims to design a web-based project management system using Laravel 12, Filament Shield, and Tailwind CSS. The research methodology employs waterfall SDLC with problem identification, data collection, UML system design, and black box testing stages. The system is designed with an Role-Based Access Control (RBAC) for 6 roles: Super Admin, Project Manager, Team Lead, Developer, QA Tester, and Client. Results demonstrate successful system implementation with integrated platform features, multi-level RBAC, real-time tracking through kanban dashboard, and responsive interface. Black box testing with 21 test cases covering 5 core system functions (authentication, RBAC, project CRUD operations, task management, and kanban board) achieved 100% success rate. The system successfully addresses progress tracking and coordination issues with an integrated solution supporting organizational scalability